2018
DOI: 10.14295/oh.v24i1.1131
|View full text |Cite
|
Sign up to set email alerts
|

Development and quality of gladiolus stems with the use of vermicompost and Trichoderma sp. in substrate

Abstract: The gladiolus is an important cut flower that is cultivated in all parts of the world, and it is very appreciated to be used in floral arrangements. The growing concern with the environmental contamination and the look for production with higher quality have resulted in increasing the number of studies on the use of organic inputs and microorganisms in floriculture, in particular, the vermicompost and the Trichoderma sp. This work was conducted with the objective to evaluate the development and the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…The plants treated with any concentration of vermicompost had significantly higher values for growth and flowering traits compared to control plants. These findings are similar to those obtained by earlier researches on ornamental plants including Gladiolus grandiflorus (Cruz et al, 2018;Karagöz et al, 2019), Tagetes erecta (Kumar et al, 2019), Gerbera jamesonii (Arunesh et al, 2020) and Chrysanthemum morfolium (Padamanabhan, 2021;Yadav and Chandla, 2021).…”
Section: Effect Of Vermicompost Treatmentssupporting
confidence: 91%
“…The plants treated with any concentration of vermicompost had significantly higher values for growth and flowering traits compared to control plants. These findings are similar to those obtained by earlier researches on ornamental plants including Gladiolus grandiflorus (Cruz et al, 2018;Karagöz et al, 2019), Tagetes erecta (Kumar et al, 2019), Gerbera jamesonii (Arunesh et al, 2020) and Chrysanthemum morfolium (Padamanabhan, 2021;Yadav and Chandla, 2021).…”
Section: Effect Of Vermicompost Treatmentssupporting
confidence: 91%
“…The plants treated with T. harzianum and pruned most severely grew taller and had greater trunk diameters than those pruned less heavily and not inoculated. On the contrary, Cruz et al [41] did not observe any effect of Trichoderma spp. on the length of shoots or the flower quality of gladiolus.…”
Section: Growth and Flowering Of Plants After Application Of Trichode...mentioning
confidence: 87%
“…do not always affect the quality of flowers and inflorescences in Gladiolus. The experiment conducted by da Cruz et al [42] on the 'Peter's Pear' cultivar showed no effect of the fungal treatment on the plants. The researchers stressed the fact that Freesia reflacta 'Argentea' produced inflorescences with the most flowers after Trichoderma fungi had been applied in treatment with plant lighting.…”
Section: Earliness Of Flowering and Quality Of Flowers And Plantsmentioning
confidence: 89%